Control of cryogenic extractive distillation process for separating CO2–C2H6 azeotrope. (2nd September 2019) - Wang, Haiqin; Fan, Minglong; Zhang, Zubin; Hao, Jingyu; Wang, Ce
Highlights: A four-column extractive distillation system using natural gas liquid as heavy solvent is used to separate CO2 –C2 H6 azeotrope. Fixed reflux ratio and reflux/feed ratio control structure are used to investigate the controllability of four-column extractive distillation. The reflux/feed ratio controller of four columns can adjust the reflux ratio in real time according to the disturbance of feed flow and composition, which greatly improves the stability of the top distillation products purity. Abstract: The existence of heterogeneous azeotrope of CO2 –C2 H6 makes it difficult to separate CO2 from the hydrocarbons in the associated gas by cryogenic extractive distillation process. A four-column extractive distillation system using natural gas liquid as heavy solvent is used to separate CO2 –C2 H6 azeotrope. Carbon dioxide, ethane, propane and butane are recovered from the top of the extractive distillation column, deethanizer, depropanizer and debutanizer respectively. The C3 + hydrocarbon mixture called natural gas liquid is recovered at the bottom of the debutanizer, one part of which is transported as NGL product and the other part is pumped back near the top of the extractive distillation column as solvent. The purpose of this paper is to develop an effective plant wide control structure for this four-column extractive distillation system. Fixed reflux ratio and reflux/feed ratio control structure are used to investigate the controllability of four-column extractive distillation. Results show that both control structures have successfully realize the dynamic simulation of the extractive distillation process. However, under the disturbance of feed flow rate and composition, the controllability of reflux/feed ratio control structure on purity of top distillation products is better than that of fixed reflux ratio control structure. The reflux/feed ratio controller of four columns can adjust the reflux ratio in real time according to the disturbance of feed flow and composition, which greatly improves the stability of the top distillation products purity.